Performance evaluation of 5G New Radio low-density parity check codes over different scenarios of lognormal fading channel - Ali, Mohammed Hussein; Al-Rubaye, Ghanim A. (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
Low-density parity check (LDPC) is a channel coding technique widely utilized in the 5G New Radio standard, it is of utmost importance in facilitating proficient and secure communication in noisy environments by effectively minimizing errors during data transmission. It is primarily used in the 5G New Radio (NR) standard for encoding user information on the physical downlink shared channel (PDSCH). The necessity to satisfy the increasing expectations for throughput, latency, and dependability led to the decision to deploy LDPC codes for user data, especially in the enhanced mobile broadband (eMBB) and ultra-reliable and low-latency communications (URLLC) scenarios of 5G networks. The present system proposes the use of NR-LDPC codes to transmit data across a lognormal multipath fading channel model in the presence of AWGN. Wireless communication channels often use a lognormal multipath fading channel model, where the received signal experiences both multipath fading and lognormal shadowing. The research investigates the effectiveness of NR-LDPC coding in improving QAM-OFDM system performance by analyzing two rate-compatible base graphs and comparing their effectiveness with an uncoded system. This analysis is crucial for optimizing communication network design, especially in scenarios where the integrity of data is of utmost importance. We introduce a new method to improve the 5G NR LDPC code capability under lognormal fading conditions. This approach develops a layered min-sum (LMS) algorithm to provide enhanced error-correcting capabilities. The developed and implemented decoding algorithm represents a significant advancement over traditional detection methods. The outcomes of the simulation provide evidence of the effectiveness of the proposed NR-LDPC coding techniques in terms of their error correction and identification capabilities. In addition, the developed LMS decoding algorithm was shown to significantly decrease the BER of the system.